Solving the Viscous Burger Equation Using the Hopf Cole Transform - Tuz, Münevver (Tokat Gaziosmanpasa University, 2023)
In this study, the non-linear Burger equation is discussed, the equation is linearized by using the Hopf-Cole transform. With the application of this transformation, the system is turned into a Cauchy problem, the boundary conditions are created and the solution is made, and the moving wave solutions are obtained. The study of these moving waves has an important place in fluid dynamics, solitary wave found. Its solutions allow us to obtain exact and real solutions for (2+1) dimensional and (3+1) dimensional nonlinear PDE types in Mathematical physics.
Keywords: Software Testing; Verification and Validation; Yazılım Testi; Doğrulama ve Validasyon